Sultan to sultan : adventures among the Masai and other tribes of East Africa - Sheldon, Mary French 1847-1936 (Adam Matthew Digital, 1892)
Accompanied by a retinue of African porters, American born, 41 year old French-Sheldon exhibits great tenacity in her journey across East Africa from the Court of the Sultan of Zanzibar to Mount Kilimanjaro. She relates her contacts with various tribes en route